Influence of temperature on CODMn and Mn2+ removal and microbial community structure in pilot-scale biofilter. (November 2020) - Cheng, Qingfeng; Liu, Zongyang; Huang, Yang; Li, Fengjiao; Nengzi, Lichao; Zhang, Jie
Graphical abstract: Highlights: Simultaneous removal of CODMn and Mn 2+ was achieved at different TWT conditions. OMOB, MnOB and other bacteria were coexisted in the biofilter. TWT was an important operational parameter to affect microbial community structure. TWT affected the activity of OMOB and MnOB. Abstract: Test water temperature (TWT) is a significant operational parameter in biofilter. In this study, a pilot-scale biofilter was established to investigate the removal efficiency of CODMn and Mn 2+ and the microbial community structure at different TWT. When CODMn and Mn 2+ in the influent were 6–8 and 0.9–1.2 mg/L, respectively, the removal rates were 22.61% and 94.28% at the low TWT, while 69.42% and 97.85% at the high TWT, respectively. Biological CODMn and Mn 2+ removal followed the first-order reaction, and at the low and high TWT, the k value was 0.00704 and 0.0738 and 0.0313 and 0.113 min −1, respectively. Organic matter oxidizing bacteria (OMOB, Sphingopyxis, Sphingomonas, Amphiplicatus, Novosphingobium, Gemmatimonas, Chryseolinea and Sphingobium ) and manganese oxidizing bacteria (MnOB, Hyphomicrobium, Pedomicrobium and Pseudomonas ) were coexisted in 0–1.5 m of the biofilter bed at the low and high TWT, and the abundances were not the main factor affecting the removal efficiency, however the activity.